Principles of financial engineering - Neftci, Salih N. (San Diego, Calif. : Elsevier Academic Press, 2004)
The book offers a clear links between intuition and underlying mathematics and an underlying mathematics and an outstanding mixture of market insights and mathematical material.
Includes bibliographic references and index.
uaj 20/02/2015
Loan
Keywords: Financial engineering